PERLINDUNGAN PERAWAT PEREMPUAN DI RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA TAHUN 2011 - Suryani, Dyah (Universitas Ahmad Dahlan, 2012)
The population of Indonesia is very large, the majority are women, if properly guided anddirected it will be workers who are very favorable for development efforts. Protection policiesthat are specific to women workers in addition directed to ensure the safety and healthassociated with reproductive functions inherent in self female workers also unsure equality ofemployment opportunities and the security treatment without discrimination in the workplace(equality and gender justice). As a saveguard against the work need to be increased throughimproved working condition, working condition, as mell as working relationship in order toimprove the welfare of workers as a whole and for workers and protection of women need to beconsidered in accordance with the status and dignity. PKU Muhammadiyah Hospital inYogyakarta that is one of the mayor hospitals in Yogyakarta City are certainly a lot of hiringnurse with the number of male nurse as many as 175 people and nursing women as many as226 people. By employing female nurse was then the hospital must also provide the rights ofwomen to nurse in accordance with the minimum set by law. The purpose of this study was tofind out execution protection against female nurses in PKU Muhammadiyah Hospital inYogyakarta.The subject of this study was female nurses who were taken asa many as 3 people endthe head of personal. Data taken by the interview guide. This was qualitative research. Dataanalysis was done by using an explanation (explanation building).Implementation of working time there is excess of 2 hours for shift 3 (night) that have notbeen counted as overtime, RSU PKU Muhammadiyah imposed only official holiday for 3 day,the granting of maternity leave / birth / biological autumn, annual leave has been granted inaccordandance with the regulations, provision of food and drinks for female nurses who work innight shift has not complied with, the implementation of remuneration are accordance withexisting regulations, the implementation Jamsostek compliance with regulations.